Implementasi Upah dan Pajak terhadap Peningkatan Pendapatan Perkapita di Indonesia - Qarina, Qarina (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to analyze how wages and taxes can increase per capita income in Indonesia. By using path analysis techniques (path analysis), empirically this study found the result that wages have a positive and significant effect on GDP per capita both directly and indirectly through taxes.